Double-edged sword: Persistent effects of Communism on life satisfaction - Vladimir Otrachshenko; Milena Nikolova; Olga Popova (Global Labor Organization (GLO), 2021)
Communism was a two-edged sword for the trustees of the former regime. Communist party members and their relatives enjoyed status and privileges, while secret police informants were often coerced to work clandestinely and gather compromising materials about friends, colleagues, and neighbors. We examine the long-term consequences of such connections to the communist regime for life satisfaction in Central and Eastern Europe and the former Soviet Union. We also calculate a monetary equivalent of those effects and empirically test mechanisms. The findings underscore that past communist regime connections have a persistent but differential effect on life satisfaction.
Keywords: D60; I31; N00; P26; P36; P52; 330; Communist regime; historical legacy; Eastern Europe; former Soviet Union; life satisfaction; elite networks; Communist party; informants